Optimizing Waqf Fund Management in Indonesia: An Integrated Financial Inclusion Strategy through the Blockchain - Eka Suryawijaya, Tito Wira; Oo Khant , Thant Thet; Setyo Utomo , Muhammad Tata Rizky; An'nur Iftina, Beta Salsabilla (UNIVERSITAS SERAMBI MEKKAH, 2024)
This study aims to analyze the integrated financial inclusion strategy for optimizing potential waqf funds in Indonesia. The research employs a qualitative approach, utilizing the Business Model Canvas as an analytical framework. Data collection techniques include observation, interviews, and a literature review. The findings indicate that waqf property often remains underutilized, resulting in stagnant assets. However, the collection, management, and distribution of waqf funds can significantly benefit the mauquf alayh (beneficiaries), provide greater merit to the wakif (donors), and increase the resources available to Nazir (managers). The study concludes that the Waqf Blockchain Program can enhance the efficiency of waqf property utilization, facilitate inter-institutional integration to avoid redundancy in waqf system development, and establish a supervisory role in the planning, organization, implementation, and evaluation of Nazir waqf activities. Furthermore, this program contributes to achieving the socio-economic goals of national development across short-, medium-, and long-term periods.